MARAKNYA JUDI ONLINE: UPAYA PENGENDALIAN DENGAN KAMPANYE EDUKASI PUBLIK TENTANG PENGUATAN REGULASI DAN SANKSI PIDANA - Ahmad Munawar Nuril Ibtisan; Noor Hamzah Syihabbudin; Kresno Adi Wicaksono; Muhammad Adymas Hikal Fikri (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The rise of online gambling in Indonesia in recent years has shown a significant increase, especially in Central Java and Semarang City. The development of digital technology, easy internet access, and low legal literacy among the public are the main factors accelerating the spread of this phenomenon. This study uses a mixed methods approach with a convergent design, combining quantitative and qualitative analysis to provide a comprehensive picture of the patterns of online gambling and the effectiveness of government policies in tackling it. Quantitative data was obtained by processing online news reports on the number of perpetrators, frequency of enforcement, and economic losses, while qualitative data was analyzed through content analysis of media narratives, public opinion, and statements from relevant officials. The results show that losses due to online gambling increased dramatically from 2021 to 2025, reaching Rp 600 trillion in 2024 and involving 686 defendants, including students. These findings reveal that although regulations such as the 2023 Criminal Code, the 2024 ITE Law, and PP 9/1981 have provided a strong legal basis, their implementation still faces challenges in terms of technology, law enforcement coordination, and low public legal education. This research underscores the urgency of strengthening regulations, enhancing digital forensic capabilities, and developing public education campaigns as comprehensive strategies to curb the rise of online gambling in Indonesia.